Peran Moral Pajak dalam Memediasi Religiusitas dan Pengetahuan Pajak terhadap Persepsi Atas Tax Evasion Wajib Pajak Pelaku UMKM di Tulungagung - Muhammad Ivan Aziz; Srikalimah Srikalimah; Putri Awalina (Jurnal Kendali Akuntansi, 2026)
This study aims to examine the role of tax morale in mediating the effects of religiosity and tax knowledge on perceptions of tax evasion among Micro, Small, and Medium Enterprise (MSME) taxpayers in Tulungagung Regency. This research employed a quantitative approach using a survey method by distributing questionnaires to 95 MSME taxpayers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that religiosity does not have a significant effect on tax morale but has a significant direct effect on perceptions of tax evasion. Tax knowledge has a significant positive effect on tax morale and also significantly influences perceptions of tax evasion. Furthermore, tax morale has a significant effect on perceptions of tax evasion, indicating that higher levels of tax morale are associated with a lower tendency to engage in tax evasion. The mediation analysis reveals that tax morale does not mediate the relationship between religiosity and tax evasion. However, tax morale significantly mediates the relationship between tax knowledge and tax evasion. These findings suggest that tax knowledge and tax morale are critical factors in reducing tax evasion among MSME taxpayers. Meanwhile, religiosity exerts a direct influence on tax evasion perceptions without operating through the mechanism of tax morale. Therefore, enhancing tax literacy and strengthening tax morale represent effective strategies for improving taxpayer compliance and reducing tax evasion practices among MSME taxpayers.